COVID‐19 and future pandemics: A blockchain‐based privacy‐aware secure borderless travel solution from electronic health records. (22nd July 2022) - Odoom, Justice; Huang, Xiaofang; Danso, Samuel Akwasi
Abstract: COVID‐19 pandemic undoubtedly lingers on and has brought unprecedented changes globally including travel arrangements. Blockchain‐based solutions have been proposed to aid travel amid the pandemic hap. Presently, extant solutions are country or regional‐based, downplay privacy, non‐responsive, often impractical, and come with blockchain‐related complexities presenting technological hurdle for travelers. We therefore propose a solution namely, Borderless to foster global travel allowing travelers and countries collaboratively engage in a secure adaptive proof protocol dubbed Proof‐of‐COVID‐19 status a number of arbitrary statements to ascertain the fact that the traveler poses no danger irrespective of the country located. As far as we know, this is first of its kind. Borderless is implemented as a decentralized application leveraging blockchain as a trust anchor and decentralized storage technology. Security analysis and evaluation are performed proving security, privacy‐preservation, and cost‐effectiveness along with implementation envisioning it as a blueprint to facilitate cross‐border travel during the present and future pandemics. Our experimental results show it takes less than 60 and 3 s to onboard users and perform proof verification respectively attesting to real usability scenarios along with the traits of arbitrary proofs to aid responsiveness to the dynamics of pandemics and blockchain abstraction from travelers.